Tracing cross species transmission of Mycobacterium bovis at the wildlife/ livestock interface in South Africa - Sichewo, Petronillah R.; Hlokwe, Tiny M.; Etter, Eric M. C.; Miche, Anita L. (BioMed Central Ltd., 2021)
Background: Bovine tuberculosis (bTB) affects cattle and wildlife in South Africa with the African buffalo (Syncerus caffer) as the principal maintenance host. The presence of a wildlife maintenance host at the wildlife/livestock interface acting as spill-over host makes it much more challenging to control and eradicate bTB in cattle. Spoligotyping and mycobacterial interspersed repetitive unit-variable number of tandem repeat (MIRU-VNTR) genotyping methods were performed to investigate the genetic diversity of Mycobacterium bovis (M. bovis) isolates from cattle and wildlife, their distribution and transmission at the wildlife/livestock interface in northern Kwa-Zulu Natal (KZN), South Africa. Results: SB0130 was identified as the dominant spoligotype pattern at this wildlife/livestock interface, while VNTR typing revealed a total of 29 VNTR profiles (strains) in the KZN province signifying high genetic variability. The detection of 5 VNTR profiles shared between cattle and buffalo suggests M. bovis transmission between species. MIRU-VNTR confirmed co-infection in one cow with three strains of M. bovis that differed at a single locus, with 2 being shared with buffalo, implying pathogen introduction from most probably unrelated wildlife sources. Conclusion: Our findings highlight inter and intra species transmission of bTB at the wildlife/livestock interface and the need for the implementation of adequate bTB control measures to mitigate the spread of the pathogen responsible for economic losses and a public health threat.